Effect of Exogenous Human Kisspeptin-10 on Concentration of Estradiol, Progesterone and Its Response on Expression of Estrus Signs in Bhadawari Buffaloes - Mishra, Rabindra Mohan; Ravi, Sanjay Kumar; Balamurugan, B.; Yadav, Pavan Kumar; Kumar, Anshuman; Kumar, Priya Ranjan; Saraf, Kaustubh Kisor; Narwade, Priyanka; Kumari, Medha; Tiwari, Manish Kumar (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Kisspeptin is identified as a neuropeptide having its response on various endocrines leading to significant impact on reproductive physiology in livestock. The aim of the research was to evaluate the effect of Human Kisspeptin-10 (hKp10) on the concentration of plasma estradiol (E2), progesterone (P4) and visual estrus signs in cyclic Bhadawari buffalo. Four cyclic Bhadawari buffaloes pre-fitted with jugular cannula were administered hKp10 @ 1.5, 2.5, 5 µg/ kg body weight (bw) and 2ml normal saline (NS) as a control on D10 of estrous cycle (D0- Day of estrus) in a fashion that none of the buffaloes received the same dose twice. All experimental buffaloes received all the hKp10 doses and/ or NS at least once at 2 days interval. Blood samples were collected in heparinised tubes at -60, -30, 0 (just before injection of hKp10), 15, 30, 45, 60, 90 and 120 minutes (min.) after the hKp10 and/ or NS injection. Plasma was separated and stored at -200 C. Estimation of plasma E2 and P4 was done using ELISA kit. There was non-significant (P>0.05) increase in the level of plasma E2 and P4 at 1.5, 2.5 and 5µg/ kg body weight of hKp10 doses in the treated buffaloes compared to control (NS infused). The response on visible estrus signs were significant when observed between untreated (control group) and hKp10 treated estrous cycle. Kisspeptin might be used to address reproductive constraints like weak or silent estrus in Bhadawari Buffaloes.